UMA ANÁLISE DOS DIFERENTES TIPOS DE AGENTES CONTRATANTES DAS EQUIPES DE ATENÇÃO BÁSICA NO BRASIL E CERTIFICAÇÃO DE QUALIDADE - Thaís dos Santos Gomes (2018)
After World War II, there was an acceleration of technological development, triggered by the association between scientific knowledge and industrial production, from which the world economic system underwent a deep transformation, becoming more integrated and competitive. Such a change in the world order, associated with the oil crises throughout the 1970s, led states to crisis in their interior. In the following years, the major international banks argued that states should be reformed to be able to overcome the deep crises of the period. In the late 1980s, Brazil underwent a process of re-democratization of the country. After 20 years of Military Regime, one called for better conditions, especially in the field of social sciences. In 1988, in the Federal Constitution of Brazil, health won a section, which laid the foundations for the creation of the Unified Health System (UHS). However, although health was recognized as a right for all and the duty of the State, the Constitution left the private sector in the area. Linked to this, in the 1990s, when the then President of the Republic of Brazil, Fernando Henrique Cardoso, came to power, the State Counter-Reformation process began, which transferred to non-state entities the provision of services that were not exclusive to the Public Power. Thus, Third Sector organizations were qualified to work in health. These non-profit entities have grown dramatically in Brazilian basic care, but in addition to their positive aspects, many negative critics have also been raised, showing that these may jeopardize the consolidation of compliance with UHS guidelines. From this, it is imperative to carry out studies that seek to understand the impact of these services on the quality of health offered and the strengthening of UHS. This study aims to verify the existence of an association between the new forms of private management in the UHS, basic care in Brazil, and the quality of care offered, identifying in which dimensions of quality there are possible differences in relation to public management. It is an observational study, with a descriptive and inferential approach. The variables were obtained from databases of the Program for Improvement of Access and Quality of Basic Care (PIAQ-BC) and the National Registry of Health Establishments (NRHE), of the Ministry of Health. First at the municipal level and the second at the team level. We analyzed 4469 municipalities and 29,778 basic care teams. In the descriptive analysis the variables were distributed by units of the federation, PIAQ strata and geographic regions. In the inferential analysis, by binary logistic regression, the dependent variable was the grade obtained in the certification process of the basic care teams, and the independent variable was the contracted agent dichotomized in public and private. Data were adjusted by PIAQ strata. The results showed that the private contracting agents are concentrated in the larger municipalities with better socioeconomic development. No statistical association was found between quality certification and types of contracting agents in the analysis with the municipal data. It was verified that the best levels of certification were obtained by the larger municipalities and with greater economic dynamicity. In addition, it was identified that the highest quality of care offered in basic care is associated to the teams managed by private contracting agents, in the dimensions Access, Use, Participation and User Satisfaction; Access and Quality of Care and Organization of the Work Process; Structure and Operating Conditions of BHU and Municipal Management for the Development of Primary Care. On the other hand, it has been verified that being totally managed by public contracting agents is related to obtaining better grades with respect to the Valorization of the Worker. Thus, considering the intense struggle in the construction and structuring of the UHS and the risks to its consolidation as a universal, equitable and equitable policy, the results pointed out the need for debate and policy formulation. Above all, with the purpose of increasing the access and quality of health services managed directly by the public power guaranteeing greater effectiveness of the care offered. In addition, it is advocated the need for other studies aimed at demystifying this field of study, still obscure, especially in the ambit of the PIAQ.